Сигнальные индикаторы турбулентности рынков - Семеняк, И. В.; Мангушев, Дмитрий Валерьевич; Семеняк, І. В.; Мангушев, Дмитро Валерійович; Semenyak, I. V.; Mangushev, Dmitro V. (Харків : Харкiвський нацiональний унiверситет iмені В. Н. Каразiна, 2008)
Рассмотрено два фактора, которые оказывают существенное влияние на устойчивость и проявления турбулентности украинского рынка: индекс человеческого развития и импортные потоки. Сделаны выводы важные для выбора идентификаторов воздействия на рынок факторов турбулентности.

Розглянуто два фактори, які впливають на стійкість і прояви турбулентності українського ринку: індекс людського розвитку та імпортні потоки. Зроблено висновки важливі для вибору ідентифікаторів впливу на ринок факторів турбулентності.

There are studied two factors which have an essential influence on the stability and development of the turbulence of the Ukrainian market: the index of the human’s development and the imported flours. There are made conclusions which are important for the choice of the identifications of the influence on the market of the influent factors.
Сигнальні індикатори турбулентності ринків
Signal Indicators of Market Turbulence
Keywords: SOCIAL SCIENCES::Business and economics::Economics; индикатор; импортные потоки; индекс человеческого развития; турбулентность; рынок; індикатор; імпортні потоки; індекс людського розвитку; турбулентність; ринок; the imported flour; the index of the human’s development; the indicator; market; turbulence